Senior High School Students’ Ability in Analyzing the Poetic Elements of Poem in English - Ani Santika; Delvi Wahyuni (Journal of English Language Teaching, 2020)
This study aimed to investigate senior high school students’ ability in analyzing the poetic elements of poem in English and the difficulties faced by the students in analyzing the poetic elements of poem in English. The participants of this research were 19 eleventh grade students in SMA Pembangunan Laboratorium UNP Padang who take the English subject as their elective subject. This study is descriptive research with quantitative approach. The instrumentation of this research is test. The result showed that the level mastery of the students in analyzing the poetic element of poem in English is poor. Based on the data taken, the hardest poetic element for students is onomatopoeia and the easiest is simile. And it can be concluded that students' ability in analyzing the poetic elements of poem in English is and students have difficulty in analyzing poetic elements.Key words: ability, difficulties, poetic elements